Individual activation of dementia sufferers in a home setting: A randomized controlled study Einzelaktivierung von Menschen mit Demenz im häuslichen Setting: Eine randomisierte kontrollierte Studie - Stemmer, Renate; Grässel, Elmar; Schmid, Martin (Zeitschrift für Gerontologie und Geriatrie, 2019)
Background and objectives: The present project investigated the hypothesis that a multimodal individual activation of people with mild to moderate dementia in the home setting during a 6-month intervention period leads to improved everyday practice and cognitive abilities compared to the control group. Material and methods: Intervention: a practical activation was performed by relatives 6 days per week. Cognitive stimulation took place once a week and was done by an external person. The relatives were trained and counselled by project staff. Evaluation: a multicentric randomized controlled trial (RCT) with total sample size of 72 participants suffering from dementia with a mini-mental state test (MMST) ≤24 and ≥12. Of the participants 36 were in the intervention group and 36 in the control group: intervention and follow-up periods each took 6 months. Primary outcome variables: activities of daily living (ADL) abilities (E-ADL test) and cognitive abilities (ADAS-Cog); secondary outcome variables: care dependency scale (PAS) and geriatric symptoms including instrumental abilities (NOSGER scale incl. IADL-test), quality of life (WHOQOL-BREF) and stress for the informal caregivers scale (HPS). The evaluation was carried out as a pre-post analysis (t 0 /t 1 /t 2 ) using comparison of means for the differences between the pretest and posttest values. Results: After the end of the 6‑month intervention period (t 1 ), there were positive effects on the ADL skills of people with mild dementia (Cohens d = 0.37) but no effects on the ADL skills of people with moderate dementia (Cohens d = 0.00). In terms of cognitive abilities, mild effects (Cohens d = 0.26) were found in people with moderate dementia but not in mild dementia (Cohens d = 0.04). The results are not significant. Caring dependency results in a non-significant effect in mild dementia (Cohens d = 0.33) and a significant effect in moderate dementia (Cohens d = 0.87, p = 0.025, Mann-Whitney U‑test). The NOSGER subscale social behavior showed a strong significant effect in moderately severe dementia (Cohens d = 1.03, p = 0.013) but 6 months after the end of the intervention (t 2 ) these effects were no longer detectable. With respect to the activating relatives no effects could be detected. Conclusion: The hypothesis could not be confirmed. Since the target sample size was not reached, significant results were not expected. Nevertheless, the calculation of the effect sizes provides indications of possible effects of multimodal activation.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Activities of daily living; Cognitive dysfunction; Informal care; Multimodal activation; Quality of life